Reference skills for the school librarian tools and tips - Riedling, Ann Marlow 1952-; Houston, Cynthia (Santa Barbara, California Libraries Unlimited, an imprint of ABC-CLIO, LLC, 2019)
"This basic text is designed to teach reference skills to school librarians."--Provided by publisher.
Reference and the school library : an overview -- Selection, evaluation, and maintenance of the reference collection -- Bibliographies -- Ready reference tools: Fact books, directories, almanacs, yearbooks, and handbooks -- Biographical sources -- Dictionaries and encyclopedias -- Geographical sources -- Electronic indexes and abstracts, periodical and specialized databases -- The reference interview -- The Internet in today's reference services -- Scenarios and exercises.
Includes bibliographical references (pages 121-124) and index.
Keywords: School libraries -- Reference services -- United States; Children's reference books; Children's electronic reference sources; Internet in school libraries